Host RNA-Binding Proteins as Regulators of HIV-1 Replication - Sebastian Giraldo-Ocampo; Fernando Valiente-Echeverría; Ricardo Soto-Rifo (Viruses)
RNA-binding proteins (RBPs) are cellular factors involved in every step of RNA metabolism. During HIV-1 infection, these proteins are key players in the fine-tuning of viral and host cellular and molecular pathways, including (but not limited to) viral entry, transcription, splicing, RNA modification, translation, decay, assembly, and packaging, as well as the modulation of the antiviral response. Targeted studies have been of paramount importance in identifying and understanding the role of RNA-binding proteins that bind to HIV-1 RNAs. However, novel approaches aimed at identifying all the proteins bound to specific RNAs (RBPome), such as RNA interactome capture, have also contributed to expanding our understanding of the HIV-1 replication cycle, allowing the identification of RBPs with functions not only in viral RNA metabolism but also in cellular metabolism. Strikingly, several of the RBPs found through interactome capture are not canonical RBPs, meaning that they do not have conventional RNA-binding domains and are therefore not readily predicted as being RBPs. Further studies on the different cellular targets of HIV-1, such as subtypes of T cells or myeloid cells, or on the context (active replication versus reactivation from latency) are needed to fully elucidate the host RBPome bound to the viral RNA, which will allow researchers and clinicians to discover new therapeutic targets during active replication and provirus reactivation from latency.